2013
DOI: 10.1002/adom.201300190
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Terahertz Bandwidth and Power from GaAsBi‐based Sources

Abstract: Terahertz photoconductive (PC) switches are popular for THz wave generation. Unlike nonlinear crystals, they don't require high optical excitation power and precise phase matching, but their output THz power is limited. Here, the conventional substrate is replaced with enhanced GaAsBi (growth recipe included) and its performance is compared to that of a LT‐GaAs PC switch and a nanoplasmonic PC switch. The results show a 0.5 THz increase in bandwidth and 4‐fold improvement in emission power for GaAsBi and GaAsB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…Numerous researchers have shown that on of the most effective implementation of dipole NAs in the THz photoconductive antennas and photomixers are arrays of metal dipoles whose length is of the order of the gap size between the electrodes. Arrays of dipole plasmonic NAs have received the name of plasmonic gratings or plasmonic nanorod gratings .…”
Section: Hybrid Photoconductive Thz Antennasmentioning
confidence: 99%
“…Numerous researchers have shown that on of the most effective implementation of dipole NAs in the THz photoconductive antennas and photomixers are arrays of metal dipoles whose length is of the order of the gap size between the electrodes. Arrays of dipole plasmonic NAs have received the name of plasmonic gratings or plasmonic nanorod gratings .…”
Section: Hybrid Photoconductive Thz Antennasmentioning
confidence: 99%
“…Previously, nanoplasmonic structures have been investigated to enhance the performance of THz detectors [17][18][19]. The main advantage of the nanoplasmonic structure for detection is to create a fast sweep out time, and thereby allow for the usage of a low-cost high-mobility long carrier lifetime substrate like semi-insulating GaAs [18,[20][21][22], as opposed to other less common substrates with short carrier lifetimes (such as low-temperature GaAs or GaBiAs) [23][24][25][26][27][28][29][30][31].…”
Section: Introductionmentioning
confidence: 99%
“…The Bi isoelectronic incorporation results in the dilute‐Bi compounds whose bandgap shrinks significantly because mainly of the anticrossing interaction between Bi 6p orbit level and valence band maximum . The bandgap shrinkage of dilute‐Bi advances the applications on infrared optoelectronic devices such as laser diode, light emitting diode, photodetector, and terahertz devices . The Bi surfactant effect is due to the Bi segregation on surface leading to the changes of growth dynamics and free energy during growth, and hence Bi is usually used as catalyst for microstructure regulation and morphology modification in semiconductors …”
Section: Introductionmentioning
confidence: 99%